1996
DOI: 10.1111/cei.1996.104.s1.3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of action of intravenous immune globulin in immune-mediated diseases

Abstract: Intravenous immune globulin (IVIG) exhibits a number of immunomodulatory properties that are mediated by the Fe portion of IgG and by the spectrum of variable (V) regions contained in the immune globulin preparations. Five predominant and non‐exclusive mechanisms of action have been proposed to account for the immunomodulatory effects of IVIG in immune‐mediated diseases: (i) functional blockade of Fe receptors on splenic macrophages: (ii) inhibition of complement‐mediated damage, an effect that is dependent on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(97 citation statements)
references
References 52 publications
1
94
0
2
Order By: Relevance
“…Studies have shown that IVIG contains antibodies against surface molecules such as MHC class I and II, Fas, CD3, CD4, CD5, CD8, T-cell receptor, interleukin-1 (IL-1), IL-6, interferon and sialic acid binding immunoglobulin-like lectin (Siglec)-8 and Siglec-9. [18][19][20][21]. On the other hand, it was reported that IVIG blocked CD95-mediated keratinocyte apoptosis possibly by the presence of antagonistic anti-CD95 antibodies [22].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that IVIG contains antibodies against surface molecules such as MHC class I and II, Fas, CD3, CD4, CD5, CD8, T-cell receptor, interleukin-1 (IL-1), IL-6, interferon and sialic acid binding immunoglobulin-like lectin (Siglec)-8 and Siglec-9. [18][19][20][21]. On the other hand, it was reported that IVIG blocked CD95-mediated keratinocyte apoptosis possibly by the presence of antagonistic anti-CD95 antibodies [22].…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for the supplemental use of IVIG is that this kind of treatment has been reported to have therapeutic benefits in severe sepsis, though it utility in treating septic patients is still a matter of discussion [24]. IVIG may modify the immunological cascade in sepsis and restore compromised defense systems [25]. However, in the past the varying results of several clinical studies assessing the beneficial effect of adjunctive immunoglobulin treatment in sepsis have been disappointing [26].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple mechanisms have been postulated to explain a putative favorable effect of IVIG in the management of STSS [58]. IVIG neutralizes the superantigenic effect of the streptococcal toxins [59] and strongly inhibits the production of TNF and interleukins.…”
Section: Intravenous Immunoglobulinsmentioning
confidence: 99%